Development and psychometric evaluation of a quality nursing care scale from nurses' perspective. Issue 4 (20th February 2021) - Liu, Ying; Aungsuroch, Yupin; Gunawan, Joko; Sha, Liyan; Shi, Tieying
Abstract: Aim: To develop and evaluate psychometric property of quality nursing care scale (QNCS) from nurses' perspective in the Chinese context. Design: A cross‐sectional survey design. Methods: This study was conducted in two phases. In Phase I, literature review and interviews were conducted to develop the items. In Phase II, content validity was evaluated by five experts. Construct validity was tested through exploratory factor analysis (EFA) among 302 nurses and confirmatory factor analysis (CFA) among 510 nurses from October 2014 to January 2015. Additionally, internal consistency reliability was tested. Results: The EFA extracted six factors including staff characteristics, task‐oriented activities, human‐oriented activities, physical environment, patient outcomes and precondition. All six factors accounted for 74.78% of the total variance to explain quality nursing care. The modified measurement model of the final version of QNCS was supported by the CFA with 48 items in six dimensions. The internal consistency reliability of final QNCS was acceptable.